The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.4236/ojpchem.2012.24019
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of a New Cellulose Acetate-Propionate Gel: Crosslinking Density Determination

Abstract: Crosslinking is one of the most commonly reactions used to improve the physical properties of cellulose derivatives. Cellulose Acetate Propionate (CAP) is a commercial ester obtained as a cellulose derivative and it can be used as basis for the synthesis of crosslinked chains as described in this work. Typical used crosslinkers are di-functional compounds, such as dianhydrides or diisocyanate. The formation of polymeric 3D structures as described in this work occurs typically by the reaction of the linear chai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…However, the 11 overuse of synthetic fertilizers and excess leaching from soils 12 has generated serious environmental impacts worldwide such as 13 the eutrophication of estuaries and other coastal regions. While 14 reducing fertilizer application can compromise crop productivity, 15 reducing nutrient losses in fertilizer application by using 16 substrates that perform controlled-release or slow-release while 17 conserving soil moisture is considered a promising alternative 18 [1,2].…”
mentioning
confidence: 99%
“…However, the 11 overuse of synthetic fertilizers and excess leaching from soils 12 has generated serious environmental impacts worldwide such as 13 the eutrophication of estuaries and other coastal regions. While 14 reducing fertilizer application can compromise crop productivity, 15 reducing nutrient losses in fertilizer application by using 16 substrates that perform controlled-release or slow-release while 17 conserving soil moisture is considered a promising alternative 18 [1,2].…”
mentioning
confidence: 99%
“…5(b), the PMMA/CAP10% blend TGA and DTG diagrams show two thermal degradation stages. The first at 310 °C with a total mass loss of ≈1% was caused by the degradation of the substitute parts of the CAP chain, and the second at 400 °C with a total mass loss of ≈98% is attributed to the degradation of the blend backbone (polymer main chain) (Jeon et al 2012;Allue and Botaro 2012). The TGA trace shows that PMMA has a high residue (7.1853%) and thermal stability than the PMMA/CAP10% blend (0.6222%).…”
Section: Thermogravimetric Analysismentioning
confidence: 98%
“…CA can be used in a variety of processes such as nano filtration and reverse osmosis, and in the production of numerous materials, such as dialysis membranes, matrices for the controlled release of drugs, fabrics for the textile industry, packaging, photographic films, and cigarette filters . In recent years, our research group has specialized in preparing polymeric networks known as gels, derived from commercial CA and used in a range of important applications . The gels are polymeric networks formed by covalent bonds or physical interactions between constituent chains, and they can be obtained from natural or synthetic polymers.…”
Section: Introductionmentioning
confidence: 99%
“…The links between polymer chains can be of first‐order and involve chemical modifications of functional groups or of second‐order and involve polar groups or hydrogen bonds . Many past studies have demonstrated important applications for the gels in general and specifically for those obtained from cellulose derivatives such as CA . Recent research in hydrogels has focused on finding materials that are biocompatible and for application in the fields of pharmaceutics, medicine, and nutrition .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation